Exomer Is Part of a Hub Where Polarized Secretion and Ionic Stress Connect - Moro, Sandra; Moscoso-Romero, Esteban; Poddar, Abhishek; Mulet, Jose M.; Perez, Pilar; Chen, Qian; Valdivieso, M.-Henar (Frontiers in Microbiology, 2021)
Plasma membrane and membranous organelles contribute to the physiology of the Eukaryotic cell by participating in vesicle trafficking and the maintenance of ion homeostasis. Exomer is a protein complex that facilitates vesicle transport from the trans-Golgi network to the plasma membrane, and its absence leads to the retention of a set of selected cargoes in this organelle. However, this retention does not explain all phenotypes observed in exomer mutants. The Schizosaccharomyces pombe exomer is composed of Cfr1 and Bch1, and cfr1D and bch1D were sensitive to high concentrations of potassium salts but not sorbitol. Additionally, they were slightly sensitive to CaCl2 and hygromycin B and resistant to LiCl. Our results showed that ATPase activity was higher in mutants than in the wild-type, pointing to membrane hyperpolarization that causes an increase in intracellular K+ content. Additionally, in response to K+ shock, the intracellular calcium level of cfr1D cells increased significantly more than in the wild-type, likely due to the larger calcium spikes in the mutant. Microscopy analyses showed that there was an increase in the intracellular Cta3 and Pkd2 pools in the mutants, which were partially diverted from the trans-Golgi network to the prevacuolar endosome. This was accompanied by a defective endosomal morphology. Despite this, most Cta3 and Pkd2 were delivered to the plasma membrane at the cell growing sites, showing that their transport from the trans-Golgi network to the cell surface occurred in the absence of exomer. Nevertheless, shortly after gene expression in the presence of KCl, the polarized distribution of Cta3 and Pkd2 in the plasma membrane was disturbed in the mutants. Finally, the use of fluorescent probes suggested that the distribution and dynamics of association of some lipids to the plasma membrane in the presence of KCl were altered in the mutants. Thus, exomer participation in the response to K+ stress was multifaceted. These results supported the notion that exomer plays a general role in protein sorting at the trans-Golgi network and in polarized secretion, which is not always related to a function as a selective cargo adaptor.